Reduction of the Roundabout Capacity Due to a Strong Stream of Pedestrians and/or Cyclists - Tomaž Tollazzi (Promet - Traffic&Transportation, 1970)
Single-lane roundabouts may face the problems of gettingcrowded and empty in their circulatory roadway due to a strongstream of pedestrians and/or cyclists.Vehicles at the roundabout entries or exits have to providethe right of way over pedestrians and/or cyclists. Therefore, itcomes to disturbances and traffic jams.If there are jams at the entry carriageway, vehicles are unableto get into roundabouts. If there are jams at the exit carriageway,vehicles are not able to leave the roundabout. U'henthe length of vehicle platoon at the exit is so long that it reachesthe preceding entry, the roundabouts suffer from getting fullyovercrowded.The paper presents the methodology of calculating the reductionof the roundabout capacity due to the pedestrian or cycliststream.The method of calculating the reduction of the roundaboutcapacity with the disturbed streams may be used for roundaboutsin urban environments, where the strength of the cyclistor pedestrian streams is not negligible.